PENGARUH KADAR DEBU KAYU TERHADAP KELUHAN PERNAFASAN PEKERJA (Studi Kasus di Home Industry Rebana Dusun Kaliwot Desa Bungah Kecamatan Bungah Kabupaten Gresik Tahun 2016) - Ma‟rifatur Rohmah; Imam Thohari; Bambang Sunarko (GEMA LINGKUNGAN KESEHATAN, 2017)
ABSTRACTBungah is a village and sub-district in Gresik Regency, East Java province, Indonesia. DesaBungah is well-known as a center of production for „kopyah‟ (a local term for cap) and tambourines. Sincethe 50s the people of Bungah made the business of producing tambourines as their livelihood. Thisbusiness continues to grow along with the increasing number of tambourine craftsmen, mainly found inwestern part of Bungah in Dusun Kaliwot. Currently, tambourines made in Bungah already spread toalmost all parts of Indonesia. The purpose of the present study was to determine the effects of the levelsof wood dust on workers‟ respiratory complaints.This is an analytic study, that attempts to explore how and why a health phenomenon occur.Subsequently, it analyzes the dynamics of correlation between the risk and effect factors.Results showed that the individual level of dust measured in 38 workers of tambourine homeindustry in Dusun Kaliwot was eligible (52.6%). Furthermore, most of those 38 workers had severerespiratory complaints (36.8%).The owners of tambourine home industry are recommended to provide their workers with masksto minimize dust exposure and to prohibit smoking at work. Workers are expected to wear masks and notsmoke during working hours. The Office of Industry and Trade is expected to monitor and control thelevels of dust in the workplace. Future researchers are expected to investigate the ambient dust levelsaround the home industry.Keywords : Tambourine home industry, levels of wood dust, respiratory complaints